UDK 547.96 Kimyo va kimyoviy texnologiyalar: Determination of optimal conditions for the extraction of gelatin from secondary local raw materials - Khusenov, Arslonnazar; Ashurov, Mirshod; Abdullaev, Otabek; Rakhmanberdiev, Gappar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Objective. This article presents the experimental results of extracting gelatin from protein-rich secondary local raw cattle skin by alkaline hydrolysis and determining the dependence of gelatin yield on the concentration of the hydrolyzing solution, temperature, and duration of hydrolysis. Also, the effect of hydrolysis conditions on the molecular weight of gelatin has been studied.